Electronic‐State Manipulation of Surface Titanium Activates Dephosphorylation Over TiO2 Near Room Temperature. (14th June 2021) - Wang, Quan; Yi, Xianfeng; Chen, Yu‐Cheng; Xiao, Yao; Zheng, Anmin; Chen, Jian Lin; Peng, Yung‐Kang
Abstract: Dephosphorylation that removes a phosphate group from substrates is an important reaction for living organisms and environmental protection. Although CeO2 has been shown to catalyze this reaction, cerium is low in natural abundance and has a narrow global distribution (>90 % of these reserves are located within six countries). It is thus imperative to find another element/material with high worldwide abundance that can also efficiently extract the phosphate out of agricultural waste for phosphorus recycle. Using para ‐nitrophenyl phosphate ( p ‐NPP) as a model compound, we demonstrate that TiO2 with a F‐modified (001) surface can activate p ‐NPP dephosphorylation at temperatures as low as 40 °C. By probe‐assisted nuclear magnetic resonance (NMR), it was revealed that the strong electron‐withdrawing effect of fluorine makes Ti atoms (the active sites) on the (001) surface very acidic. The bidentate adsorption of p ‐NPP on this surface further promotes its subsequent activation with a barrier ≈20 kJ mol −1 lower than that of the pristine (001) and (101) surfaces, allowing the activation of this reaction near room temperature (from >80 °C). Abstract : We demonstrate for the first time that TiO2 with a F‐modified (001) surface can activate p ‐NPP dephosphorylation near room temperature. The electron‐withdrawing effect of fluorine imposed on the TiO2 (001) surface strongly manipulates the electronic state of surrounding Ti5C atoms by making them very acidic, facilitating not only the bidentate adsorption of p ‐NPP but also its subsequent activation.